Mendidik Anak Secara Islami - Ilyas Rifa'i (STAI Siliwangi Bandung, 2016)
Educating children in Islam means is the duty of every Muslim. Every parent should make the Muslim religion as a basic guideline in educating and raising their children so that they will become a pious and devoted son. Islam is a religion that gives great attention to the education of children. Islam has given perfect guideline in all aspects of life, including the education of children. So that the children will eventually grow into children who are pious and useful in life, other than that they are also expected to become the next generation, the struggle relay holder.